Na trilha do metal: a construção de terriotorialidades das bandas de heavy metal em Belo Horizonte nos anos 1980 / On metal tracts: the construction of terriotorialities of heavy metal bands in Belo Horizonte during the 1980s - Calaça, Gleyber Eustáquio; Nascimento, Leonardo Alves; Diniz, Alexandre Magno (Caderno de Geografia, 2018)
Resumo Opresenteestudopretendeanalisarcomoocorreuoprocessodeterritorializaçãorelacionadoadistintosgruposidentitáriosvinculadosaogêneromusicalintituladoheavy-metal,nocontextodaBeloHorizontedosanos1980s.Paratal,apesquisabuscasuporteemconceitosdaGeografiaCulturaledaAntropologia,necessários àcompreensãodadistribuiçãoespacialdoMetalbelo-horizontino.Otrabalho faz uso deentrevistaselaboradasjuntoaosmembrosdasbandasdorecortetemporo-espacialproposto como metodologia de coleta de dados.Osresultadosindicamqueacena heavy-metaldeBeloHorizontepossuíagrandeabrangênciaterritorial, sobretudo pericentral e central, contandocomdiversosespaçosdedicadosaoestilomusical. Palavras-chave:Metal,Território, Lugar, Pedaço, Mancha, Trajeto, Circuito. Abstract The study intended to analyze how the process of territorialization related to different identity groups linked to the musical genre called heavy-metal in 1980s’ Belo Horizonte. For this, the researchers seeked support in the concepts of Cultural Geography and Anthropology, necessary to the understanding of the spatial distribution in the city. The work used interviews with members of the heavy-metal bands in Belo Horizonte as a methodology of data gathering. The results indicate that the heavy-metal scenario of Belo Horizonte had a great territorial coverage, mainly pericentral and central, counting on several spaces dedicated to the musical style. Keywords: Metal, Territory, Place, Piece, Spot, Path, Circuit. <p class="MsoBodyText" style="margin-top: .45pt; margin-right: 0cm; margin-bottom: .0001pt; margin-left: 0cm; text-align: justify; text-indent: 0cm; punctuation-wrap: simple; mso-line-break-override: restrictions;"> Palavras-chave:Metal,Território,Lugar,Pedaço,Mancha,Trajeto,Circuito.